Quantification of aldehyde terminated heparin by SEC-MALLS-UV for the surface functionalization of polycaprolactone biomaterials - Irvine, Scott Alexander (2017)
A straight forward strategy of heparin surface grafting employs a terminal reactive-aldehyde group introduced through nitrous acid depolymerization. An advanced method that allows simultaneously monitoring of both heparin molar mass and monomer/aldehyde ratio by size exclusion chromatography, multi-angle laser light scattering and UV-absorbance (SEC-MALLS–UV) has been developed to improve upon heparin surface grafting. Advancements over older methods allow quantitative characterization by direct (aldehyde absorbance) and indirect (Schiff-based absorbance) evaluation of terminal functional aldehydes. The indirect quantitation of functional aldehydes through labeling with aniline (and the formation of a Schiff-base) allows independent quantitation of both polymer mass and terminal functional groups with the applicable UV mass extinction coefficients determined. The protocol was subsequently used to synthesize an optimized heparin-aldehyde that had minimal polydispersity (PDI < 2) and high reaction yields (yield >60% by mass). The 8 kDa weight averaged molar mass heparin-aldehyde was then grafted on polycaprolactone (PCL), a common implant material. This optimized heparin-aldehyde retained its antithrombin activity, assessed in freshly drawn blood or surface immobilized on PCL films. Anticoagulant activity was equal to or better than the 24 kDa unmodified heparin it was fragmented from.